(2u+7)(2+u)=0

Simple and best practice solution for (2u+7)(2+u)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2u+7)(2+u)=0 equation:


Simplifying
(2u + 7)(2 + u) = 0

Reorder the terms:
(7 + 2u)(2 + u) = 0

Multiply (7 + 2u) * (2 + u)
(7(2 + u) + 2u * (2 + u)) = 0
((2 * 7 + u * 7) + 2u * (2 + u)) = 0
((14 + 7u) + 2u * (2 + u)) = 0
(14 + 7u + (2 * 2u + u * 2u)) = 0
(14 + 7u + (4u + 2u2)) = 0

Combine like terms: 7u + 4u = 11u
(14 + 11u + 2u2) = 0

Solving
14 + 11u + 2u2 = 0

Solving for variable 'u'.

Factor a trinomial.
(7 + 2u)(2 + u) = 0

Subproblem 1

Set the factor '(7 + 2u)' equal to zero and attempt to solve: Simplifying 7 + 2u = 0 Solving 7 + 2u = 0 Move all terms containing u to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2u = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 2u = 0 + -7 2u = 0 + -7 Combine like terms: 0 + -7 = -7 2u = -7 Divide each side by '2'. u = -3.5 Simplifying u = -3.5

Subproblem 2

Set the factor '(2 + u)' equal to zero and attempt to solve: Simplifying 2 + u = 0 Solving 2 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + u = 0 + -2 Combine like terms: 2 + -2 = 0 0 + u = 0 + -2 u = 0 + -2 Combine like terms: 0 + -2 = -2 u = -2 Simplifying u = -2

Solution

u = {-3.5, -2}

See similar equations:

| 6p^4+7p^2-3=0 | | 8x9/8 | | x+11=x-4 | | 5x+1=2x+37 | | 10-5x=3(x-4)-2(x+7) | | 24(7+g)=48g | | -3(3s-5)-15=-3(8s+7)-3 | | 28n^2+96+184m=0 | | 11-(-7)/-3-(-2)= | | -3y^2-6y+10=0 | | 0.12(24)+0.02x=0.04(12+x) | | 3x-2=(x-14) | | 8x-10=5x-4 | | -1/2*32x^2+1000x+0 | | 5-1/3x=-15 | | 8n-12=8n+8 | | 3/5f-7=-4 | | d/4+11=47 | | 36(p+4)=45.6p | | -8(2+7x)=-6x+30 | | 32x8/10 | | 17-3p=-4p | | 2+2h/7=-10 | | x^2+18=-6 | | (g-3)(2g^2+3g+3)= | | 16x^2=18x | | 2x+(15+4x)=9 | | m/3-7=2 | | 4.2+7z=4 | | 36(p+4)=50 | | -x^4-12x^2=27 | | -2(18-3k)=7x+2x |

Equations solver categories